Enterprises managed unconventionally (Economic and Political Thought, 2014)
The majority of enterprises in the world are conventionally managed.However, there are companies managed unconventionally, which achieveexcellent results. One of them is for example Mumbai Tiffin Box SuppliersAssociation, an Indian company known as Dabbawala. It employs mainlyilliterates, is a very simple structure and makes only one mistake in 8 milliondeliveries. Another unconventional company is Semco, a Brazilian enterpriseusing ‘radical democratic solutions’. Other firms are American W.L. Gore& Associates and Morning Star. The former gives its employees completefreedom and triggers their extraordinary involvement. The latter promotesself-management. Other firms managed unconventionally include the SpanishBanco Popular, organised in the form of a reversed pyramid, and the Polishbranch of a British firm – Hays, placing extreme trust in the employees. Allthese companies achieve extraordinary results.